Knowledge, attitudes, and practices regarding family planning among two groups of women in Erbil - Ismail, Zhian A.; ---------, Namir Al-Tawil; Hasan, Shukir S. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Family planning allows individuals and couples to anticipate and attain their desired number of children and the spacing and timing of their births. Insufficient knowledge, attitudes, and practices about the family planning and, more important, methods for family planning lead to increased number of unwanted pregnancies. The study aims at finding out the knowledge, attitudes and practices regarding family planning among two groups of women residing in two different areas (urban and rural) in Erbil city, Iraqi Kurdistan region. Methods: A cross-sectional survey was carried out during the period from November 1, 2009 and August 31, 2010. A convenience sample of 700 married women was taken from two different areas of Erbil. Results: A considerable proportion of women were unfamiliar with the term family planning, while high level of knowledge was found regarding types of contraceptives, ideal period between consecutive pregnancies, and the ideal age of pregnancy and labor. Most of the women had a positive attitude toward family planning, and knew at least one benefit of family planning to mothers and/or children. The study revealed limited effect of health education channels on the knowledge of women about family planning. The intra-uterine device and the withdrawal methods were the most popular family planning methods used among the study sample. Majority of families in both groups are currently using family planning. Conclusion: A considerable proportion of women were unfamiliar with the term family planning. Most of the women had a positive attitude toward family planning. Appropriate approaches to be used to convince the policy makers about the importance of family planning.